1997
DOI: 10.1038/sj.onc.1201147
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cell death activity promotes pulmonary metastasis of melanoma cells

Abstract: Bcl-2 inhibits apoptosis from a variety of stimuli, and a Bcl-2-binding protein BAG-1 also functions in protection from apoptosis in concert with Bcl-2. Here, we provide evidence that prolonged cell survival introduced by overexpression of Bcl-2 or BAG-1 proteins strongly promotes experimental pulmonary metastasis of melanoma B16-BL6 cells. In murine melanoma cell line B16-BL6, gene transfer-mediated expression of the Bcl-2 or BAG-1 led to prolonged cell survival against serumstarved apoptosis in vitro. The Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 14 publications
4
85
0
1
Order By: Relevance
“…To examine the potential role of BAG-1 in promoting cell migration, the MKN74 transfectants were analysed by goldparticle colloid assay with or without FBS or HGF as described previously (Takaoka et al, 1997). The MKN74-BAG-1 transfectants exhibited increased migration (approximately 2 ± 3-fold increase) as compared with the MKN74-NEO transfectants and parental MKN74 cells (Figure 2).…”
Section: Bag-1 Overexpression Promotes Mkn74 Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the potential role of BAG-1 in promoting cell migration, the MKN74 transfectants were analysed by goldparticle colloid assay with or without FBS or HGF as described previously (Takaoka et al, 1997). The MKN74-BAG-1 transfectants exhibited increased migration (approximately 2 ± 3-fold increase) as compared with the MKN74-NEO transfectants and parental MKN74 cells (Figure 2).…”
Section: Bag-1 Overexpression Promotes Mkn74 Cell Migrationmentioning
confidence: 99%
“…In transfection experiments, overexpression of BAG-1 can prolong cell survival alone or in combination with Bcl-2 overexpression. Murine melanoma B16-BL6 transfectant cells overexpressing BAG-1 have been shown to be resistant to apoptosis and exhibited enhanced pulmonary metastasis (Takaoka et al, 1997). Overexpression of BAG-1 in a human gastric cancer cell line led to prolonged cell survival against apoptosis induced by cell detachment`anoikis' and increased peritoneal dissemination in animals, which were attributed to its ability to promote cell survival in a detached state (Yawata et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence that developing resistance to common apoptotic stimuli is one of the factors that confer high metastatic capability to tumor cells (Glinsky and Glinsky, 1996;McConkey et al, 1996;Bufalo et al, 1997;Glinsky, 1997;Inbal et al, 1997;Shtivelman, 1997;Takaoka et al, 1997;Fernandez et al, 2000;Lowe and Lin, 2000;Wong et al, 2001). The apoptosis-resistant phenotype may be advantageous for tumor cells to survive in the metastatic process.…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock proteins are also required for cell survival and direct activation of these functions may also be important. Suppression of apoptosis might contribute to the ability of BAG-1 to promote metastatic spread (Takaoka et al, 1997;Yawata et al, 1998). Alternatively, increased metastasis may be mediated by enhanced cell motility (Yawata et al, 1998).…”
Section: Bag-1 Functionmentioning
confidence: 99%
“…BAG-1 enhances metastasis in experimental models (Takaoka et al, 1997;Yawata et al, 1998) and Shindoh et al (2000) demonstrated that BAG-1 was expressed in 89% of primary tumours with nodal metastasis compared to 38% of tumours without. BAG-1 expression levels were determined by densitometry and although this alleviates the subjectivity of scoring BAG-1 labelling intensity to some extent it does not give information on whether the immunoreactivity is nuclear or cytoplasmic.…”
Section: Bag-1 and Other Malignanciesmentioning
confidence: 99%